2011
DOI: 10.1002/jcp.22611
|View full text |Cite
|
Sign up to set email alerts
|

Neutral sphingomyelinase, NADPH oxidase and reactive oxygen species. Role in acute hypoxic pulmonary vasoconstriction

Abstract: The molecular mechanisms underlying hypoxic pulmonary vasoconstriction (HPV) are not yet properly understood. Mitochondrial electron transport chain (ETC) and NADPH oxidase have been proposed as possible oxygen sensors, with derived reactive oxygen species (ROS) playing key roles in coupling the sensor(s) to the contractile machinery. We have recently reported that activation of neutral sphingomyelinase (nSMase) and protein kinase C ζ (PKCζ) participate in the signalling cascade of HPV. Herein, we studied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 36 publications
9
46
0
5
Order By: Relevance
“…CFTR has been implicated in the homeostasis of sphingolipids (18,49), which have been shown to trigger caveolar TRPC6 translocation in lung endothelial cells (23) and hypoxia-induced vasoconstriction in isolated rat pulmonary arteries (19,22). Consistent with the latter reports (19), we found HPV to require nSMase but not aSMase.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…CFTR has been implicated in the homeostasis of sphingolipids (18,49), which have been shown to trigger caveolar TRPC6 translocation in lung endothelial cells (23) and hypoxia-induced vasoconstriction in isolated rat pulmonary arteries (19,22). Consistent with the latter reports (19), we found HPV to require nSMase but not aSMase.…”
Section: Discussionsupporting
confidence: 92%
“…nSMase is activated upon oxidative stress (20), possibly via arachidonic acid liberation by phospholipase A 2 (21), which all have been linked to HPV (1). In addition, ceramide accumulates in PASMCs upon hypoxia (22), mediates caveolar TRPC6 translocation in lung endothelial cells (23), and contributes to constriction of pulmonary artery rings (19,24). Although ceramide may thus potentially act as a direct mediator of HPV, it may also serve as substrate for the formation of other, bioactive sphingolipids, most notably sphingosine-1-phosphate (S1P).…”
Section: Significancementioning
confidence: 99%
“…As demonstrated very early, extracellular calcium inflow could be caused by opening of L-type calcium channels that could be activated by membrane depolarisation due to K V channel inhibition [77][78][79], while intracellular calcium release may occur mainly via ryanodine receptor (RyR) channels. Hypothetically, ROS could interact directly with L-type calcium channels or activate them via membrane depolarisation by inhibition of K V channels, which was recently shown in endothelium-denuded pulmonary arteries [125]. Redox regulation of L-type calcium channels and K V channels has been recently summarised [99,142].…”
Section: Downstream Targets Of Rosmentioning
confidence: 98%
“…In this regard, it was suggested that ROS release from mitochondria activates PKCε, which in turn activates NADPH oxidase to enhance ROS production and leads to a calcium increase [121]. Recently, PKCξ-dependent NADPH oxidase activation has been suggested to be induced by increased ceramide levels due to mitochondrial-dependent activation of neutral sphingomyelinase (nSMase) [122][123][124][125]. However, inhibition of the nSMase also decreased U46619-induced vasoconstriction in pulmonary arteries [122].…”
Section: Nadph Oxidases As Ros Sourcesmentioning
confidence: 99%
“…We have previously found that neutral SMase (nSMase)-derived ceramide acts as a critical mediator in the HPV response in rats by increasing reactive oxygen species (ROS) production via NADPH oxidase (8,14). However, the possible role of ceramide in other oxygen-sensing tissues remains to be explored.…”
mentioning
confidence: 99%